2001
DOI: 10.1017/s0016672301004992
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive compensation and human genetic disease

Abstract: SummaryThe effects of reproductive compensation on the population genetics of sex-linked recessive lethal mutations are investigated. Simple equations are presented which describe these effects, and so complement existing population genetic theory. More importantly, this type of mutation is responsible for several severe human genetic diseases such as Duchenne muscular dystrophy. It is argued that the applications of three modern reproductive technologies -effective family planning, in utero diagnosis with ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…The concept of reproductive compensation is mainly used in human genetics (Hastings, 2000, 2001) and has been applied to some mammalian species (e.g. Charlesworth, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of reproductive compensation is mainly used in human genetics (Hastings, 2000, 2001) and has been applied to some mammalian species (e.g. Charlesworth, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous theoretical and empirical studies demonstrate that reproductive compensation can play a major role in the maintenance of deleterious mutations in mammal populations (Charlesworth, 1994; Hastings, 2001; Overall et al ., 2002). Despite this potential role in mating system evolution, reproductive compensation has received little attention from plant evolutionary biologists.…”
Section: Introductionmentioning
confidence: 99%
“…In live-bearing hosts, reallocation of maternal resources from dead male embryos to their female siblings provides an additional, physiological mechanism through which kin selection could favor the evolution of male killing. In human and mammalian genetics, the term ''reproductive compensation'' is frequently used to denote a more restricted form of fitness compensation in which dead embryos are replaced by potentially viable ones (Charlesworth, 1994;Hastings, 2001). If females typically produce more embryos than they can carry to term and reproductive compensation occurs, an elevated rate of fetal mortality need not translate into a proportional decrease in the number of offspring born.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis has been verified in populations that have limited their reproductive output according to the increased likelihood of having surviving offspring, but then replace children losses during infancy. If this loss is caused by a genetic disorder then the surviving replacement is more likely to be a carrier (2/3 of surviving offspring) than a noncarrier (1/3), hence maintaining the existence of the recessive mutation in the population (Hastings, 2000(Hastings, , 2001. Further studies in U.K. Asian communities have demonstrated that reproductive compensation can effectively counteract the purging of deleterious alleles within consanguineous populations (Overall et al, 2002).…”
Section: Discussionmentioning
confidence: 99%